2004
DOI: 10.1016/s0002-9378(03)00911-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional sonographic measurement of normal fetal brain volume during the second half of pregnancy

Abstract: Sonographic measurement of fetal brain volume demonstrated an acceptable intraobserver variability and a nearly 10-fold increase during the second half of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 13 publications
6
57
1
3
Order By: Relevance
“…In comparison with other studies, our cranial volumes were larger than those reported by Roelfsema et al 4 and…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In comparison with other studies, our cranial volumes were larger than those reported by Roelfsema et al 4 and…”
Section: Discussioncontrasting
confidence: 76%
“…Prenatal assessments of fetal intracranial structures are usually performed using two-dimensional 2D ultrasound biometric measurements, and now, 3D ultrasound imaging is increasingly used as a complementary tool in fetal evaluation, offering the possibility of calculating fetal organ volumes and providing extra information on growth and maturation 2,3 . The Virtual Organ Computer-aided Analysis VOCAL software has previously been used to describe normal reference values for the cerebrum [3][4][5] and cerebellar volumes throughout gestation [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Postprocessing methods range from estimation of brain volume to an exact labeling of the boundaries in each slice to outline the brain. 68 Daily increase in cerebral tissue volume has been reported in a number of publications [66][67][68][69] with a range of 2.3 to 3.6 mL and a mean of 3.1 mL. Whereas the current study's methods were not directly comparable, because postprocessing methodology differed, daily growth rate was similar with 3.2 mL per day.…”
Section: Growth Of Total Cerebral Tissuesmentioning
confidence: 54%
“…Fetal MRI and ultrasound [66][67][68][69] have been used to estimate fetal brain volumes in normal pregnancies, and best-fit regression equations have been reported. Postprocessing methods range from estimation of brain volume to an exact labeling of the boundaries in each slice to outline the brain.…”
Section: Growth Of Total Cerebral Tissuesmentioning
confidence: 99%
“…Las curvas de normalidad en estudios previos para volumen intracraneal describen relaciones lineales estadísticamente significativas con la edad gestacional, como puede destacarse en el trabajo de Roelfsema basado en una muestra de 68 fetos (72,187,202). La finalidad de establecer la medición de este parámetro radica en la importancia de la medida de la circunferencia cefálica y del estudio Doppler del flujo sanguíneo cerebral para mantener la preservación del tejido cerebral en los fetos con retraso de crecimiento (203,204).…”
Section: Astas Anteriores De Los Ventrículos Lateralesunclassified